A Study of Strategy Preferences in English Language Teaching: Novice and Experienced Teacher - Laksmi, Ni Made Sintya; Artini, Luh Putu; Dewi, Ni Luh Putu Eka Sulistia (Universitas Pendidikan Ganesha, 2025)
Teaching strategies have evolved along with curriculum changes, especially in English language teaching. Each teacher has different preferences regarding their teaching strategies. Various factors, including the length of teaching experience, influence these differences. However, few studies still discuss the preferences of teaching strategies used by novice and experienced teachers in teaching English, especially in implementing the Merdeka Curriculum. This study aims to describe these preferences at SMPN. This study used a qualitative descriptive method. Data were collected through a checklist of teaching strategies, observations, and in-depth interviews. The subjects of this study consisted of one novice English teacher and one experienced English teacher. The results showed that both teachers applied different teaching strategies. Therefore, this study is expected to be a practical reference for choosing teaching strategies that suit the needs of students and efforts to improve the quality of education. In conclusion, there are significant differences in teaching strategy preferences between novice and experienced teachers. The implication is that the results of this study can serve as a reference for educational institutions in designing teacher development programs that emphasize hands-on practice and collaborative observation.